Lösungsentwicklung in der kollegialen Fallberatung: Interaktionsanalytische Perspektiven - Lazovic, Milica (Glottodidactica, 2025)
This paper provides an interactional-analytical perspective on the solution development phase in collegial case consultation in an internationally heterogeneous team of teachers for German as a foreign language. The study examines challenges arising in the process of co-constructive solution development, focusing on co-constructive handling of moments of irritation that arise for the case presenter in response to collegial suggestions and impulses for modifying a subjective theory. Narrative argumentation and the transformational processes experienced by case presenters form the second analytical focus. The study concludes with a call for the systematic support of teachers’ interactive competencies in the context of collaborative problem-solving.